Financial institutions management : a risk management approach - Saunders, Anthony, 1949- (Boston : McGraw-Hill, 2008)
This text focuses on managing return and risk in modern financial institutions. The central theme is that the risks faced by managers and the methods and markets through which these risks are managed are becoming increasingly similar
Saunders/Cornett, 6e Brief Contents PART ONE: Introduction 1 Why Are Financial Intermediaries Special? 2 The Financial Services Industry: Depository Institutions 3 The Financial Services Industry: Insurance Companies 4 The Financial Services Industry: Securities Firms and Investment Banks 5 The Financial Services Industry: Mutual Funds and Hedge Funds 6 The Financial Services Industry: Finance Companies 7 Risks of Financial Intermediation PART TWO: Measuring Risk 8 Interest Rate Risk I 9 Interest Rate Risk II 10 Market Risk 11 Credit Risk: Individual Loan Risk 12 Credit Risk: Loan Portfolio and Concentration Risk 13 Off-Balance-Sheet Risk 14 Foreign Exchange Risk 15 Sovereign Risk 16 Technology and Other Operational Risks 17 Liquidity Risk PART THREE: Managing Risk 18 Liability and Liquidity Management 19 Deposit Insurance and Other Liability Guarantees 20 Capital Adequacy 21 Product Diversification 22 Geographic Expansion 23 Futures and Forwards 24 Options, Caps, Floors, and Collars 25 Swaps 26 Loan Sales 27 Securitization
Includes bibliographical references and index.
Keywords: Financial institutions -- United States -- Management; Risk management -- United States; Financial services industry -- United States -- Management